دراسة مقارنة بين تعليمات الحوكمة الصادرة من مصرف قطر المركزي ونظام الحوكمة الصادر من هيئة قطر للأسواق المالية = A comparison study between governance instructions issued by Qatar Central Bank and governance system issued by Qatar financial markets authority - Ali Muhyiddin, Asma'a; Arif, Arif Ali; Hasan, Aznan; Al malahi, Abdallah Aassan (IIUM Press, International Islamic University Malaysia, 2019)
هدفت هذه الدراسة لتوضح الاختلافات الأساسية بين تعليمات الحوكمة الصادرة من مصرف قطر المركزي وتعليمات الحوكمة الصادرة من هيئة قطر للأسواق المالية، وذلك من خلال بيان مفهوم الحوكمة وإطارها التشريعي والتاريخي، وأبرز السلطات الرقابية والإشرافية العالمية والإسلامية التي اهتمت وأصدرت معايير للحوكمة، ثم ناقشت المعايير الصادرة من أبرز سلطتين رقابيتين في قطر وهما مصرف قطر المركزي وهيئة قطر للأسواق المالية، والفرق بينهما وأيهما أولى وانسب بالتطبيق من قبل المصارف القطرية سواء الإسلامية أو التقليدية، وخلصت الدراسة إلى وجود فروق أساسية فيما يخص المصارف وأن تعليمات مصرف قطر أولى بالتطبيق بالنسبة للمصارف، واتبعت الباحثة المنهج الوصفي من خلال دراسة الإطار النظري للدراسة، وتوضيح الاختلافات الأساسية من خلال المقارنة النظرية بين مبادئ الحوكمة للسلطات الرقابية والإشرافية القطرية. ******************************************************************************************* This study aims to clarified the Fundamental differences between Governance instructions issued by Qatar Central Bank and Governance System issued by Qatar Financial Markets Authority. Moreover, concept of corporate governance, legislative and historical framework, most important supervisory authorities whether global, Islamic or in Qatar are discuss. Then, it discusses the main differences between standards which issued by Qatar Central Bank and Qatar Financial Markets Authority, and whichever is Islamic Banks in Qatar should apply their Standards. The researcher used the descriptive analytical method to addressing the main principals. The analytical approach was also used by analyze the Governance instructions issued by Qatar Central Bank and Governance System issued by Qatar Financial Markets Authority